Effects of dietary Galla Chinensis tannin supplementation on immune function and liver health in broiler chickens challenged with lipopolysaccharide - Yuan, Peng; Xu, Haitao; Ma, Yuanfei; Niu, Jiaxing; Liu, Yang; Huang, Libo; Jiang, Shuzhen; Jiao, Ning; Yuan, Xuejun; Yang, Weiren; Li, Yang (Frontiers in Veterinary Science, 2023)
Herein, Galla Chinensis tannin (GCT) was examined for its influence on preventing lipopolysaccharide (LPS)-induced liver damage in broiler chickens. Approximately 486 one-day-old healthy broilers were randomly allocated to 3 treatment groups (control, LPS, and LPS + GCT). The control and LPS groups were fed a basal diet and the LPS+GCT group was fed the basal diet supplemented with 300 mg/kg GCT. LPS was intraperitoneally injected (1 mg/kg body weight BW) in broilers in the LPS and LPS+GCT groups at 17, 19, and 21 days of age. The results manifested that dietary GCT addition attenuated LPS-induced deleterious effects on serum parameters and significantly increased serum immunoglobulin and complement C3 concentrations relative to the control and LPS groups. Dietary supplementation of GCT inhibited LPS-induced increase in broiler hepatic inflammatory cytokines, caspases activities, and TLR4/NF-κB pathway-related gene mRNA expression. Therefore, 300 mg/kg GCT addition to the diet improved the immune function of broilers and inhibit liver inflammation by blocking the TLR4/NF-κB pathway. Our findings provide support for the application of GCT in poultry production.